2021
DOI: 10.1055/s-0040-1715283
|View full text |Cite
|
Sign up to set email alerts
|

Novel Endoscopic Management of Colovesical Fistula Secondary to Colonic Diverticular Disease

Abstract: Colovesical fistula (CVF) is an abnormal communication between bowel and urinary bladder. Most common cause is complicated colonic diverticular disease. The treatment of choice for CVF is surgery. Conservative treatment is reserved for highly selected patients who are unfit for definitive surgery. We report the case of an 86-year-old gentleman with multiple comorbidities, who presented with pneumaturia, fecaluria, and recurrent urinary tract infection. He was diagnosed to have sigmoid colonic diverticulosis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Mallaiyappan et al, 12 demonstrated novel endoscopic management of colovesical fistula secondary to colonic diverticular disease. They successfully managed colovesical fistula with the novel combined endoscopic approach (a simultaneous cystoscopy and flexible colonoscopy), which could be the first report from India.…”
Section: Best Endoscopy Video Articlesmentioning
confidence: 99%
“…Mallaiyappan et al, 12 demonstrated novel endoscopic management of colovesical fistula secondary to colonic diverticular disease. They successfully managed colovesical fistula with the novel combined endoscopic approach (a simultaneous cystoscopy and flexible colonoscopy), which could be the first report from India.…”
Section: Best Endoscopy Video Articlesmentioning
confidence: 99%